Tamapin, a venom peptide from the Indian red scorpion (Mesobuthus tamulus) that targets small conductance Ca2+-activated K+channels and afterhyperpolarization currents in central neurons - Pedarzani, P. (2013)
10.1074/jbc.M206465200